New finite element to model bond–slip with steel strain effect for the analysis of reinforced concrete structures - Santos, José (2022)
The influence of steel strain in bond–slip relationship has been the subject of recent literature, especially steel strain after yielding. This paper presents a new bond element for finite element packages which performs the bond–slip relationship, including steel strain effect. The developed element consists of an orthotropic four-node plane stress element whose constitutive material laws were changed. In order to verify the accuracy of this element several 2D numerical results were compared with experimental data. The results obtained with this element showed the need for its use to achieve good results and the rel evance of steel strain effect on bond–slip relationship, especially in tension elements.